Spontaneous Hyphema during Ibrutinib Treatment in a CLL Patient - Kim Abbegail Tan Aldecoa; Chef Stan L. Macaraeg; Akash Dadlani; Sri Yadlapalli (Case Reports in Hematology)
Ibrutinib is an oral, first-line, targeted therapy for chronic lymphocytic leukemia (CLL). Commonly reported adverse events are diarrhea, fatigue, and musculoskeletal pain, but rarely it has been associated with visual disturbances. Here, we present a rare case of spontaneous hyphema in a 60-year-old patient with a known diagnosis of CLL on ibrutinib treatment.